Hypermethylation of RNF125 promotes autophagy-induced oxidative stress in asthma by increasing HMGB1 stability - Jiapeng Hu; Ruiwei Ding; Shaozhuang Liu; Jia Wang; Jianjun Li; Yunxiao Shang (iScience, 2023)
Summary: Asthma is a global chronic airway disease. The expression and role of RNF125, an E3 ubiquitin ligase, in asthma remain uncertain. In this study, we revealed that RNF125 was downregulated in the bronchial epithelium of mice and patients with asthma. Rnf125 hypermethylation was responsible for the low expression of RNF125 in primary airway epithelial cells of mice treated with OVA. Moreover, we demonstrated that RNF125 could attenuate autophagy, oxidative stress, and protect epithelial barrier in vivo and in vitro. Additionally, we identified HMGB1 as a substrate of RNF125, which interacted with the HMG B-box domain of HMGB1 and induced degradation via the ubiquitin proteasome system, reducing autophagy and oxidative stress. Overall, our findings elucidated that hypermethylation of Rnf125 reduced its expression, which promoted autophagy-induced oxidative stress in asthma by increasing HMGB1 stability. These findings offer a theoretical and experimental basis for the pathogenesis of asthma.